Social, Institutional, and Personal Dimensions of Assessment Innovation Adoption in Universities - Mirfakhraei, Hoda; Ghanizadeh, Navid (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the social, institutional, and personal factors that influence university faculty members’ adoption of assessment innovations in higher education contexts. A qualitative research design was employed using semi-structured interviews to capture in-depth insights from 22 academic staff members from various universities in Tehran, Iran. Participants were purposefully selected based on their engagement with or exposure to innovative assessment practices. Interviews continued until theoretical saturation was reached. Data were transcribed verbatim and analyzed thematically using NVivo software. The analysis process included open, axial, and selective coding to identify overarching themes and subthemes across the participants’ narratives. The findings revealed three major thematic dimensions influencing assessment innovation adoption: (1) social dynamics and collaborative culture, (2) institutional structures and policies, and (3) personal beliefs and professional identity. Key social factors included collegial support, student expectations, and departmental norms, while institutional enablers and constraints such as leadership, resources, and policy alignment shaped faculty capacity to innovate. On the personal level, assessment literacy, attitudes toward change, and academic identity played a critical role in motivating or hindering the adoption of new assessment practices. These dimensions were found to be deeply interrelated, forming an ecological system of influences that collectively shaped faculty decision-making. Assessment innovation in higher education is a multidimensional process that depends not only on individual faculty willingness but also on the broader social and institutional environment. For reform to be sustained, universities must foster a culture of collaboration, provide aligned structural supports, and develop faculty capacity through targeted professional development. A systemic and coherent approach is essential for embedding innovative assessment practices within academic institutions.